A Study to Assess the Usage of Personal Protective Equipment among Health Care Providers Working in Covid-19 Wards in Pune City, Maharashtra (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: The Protective equipment consists of garments placed to protect the health care workers or anyother persons to get infected. All personal protective equipment should be safely designed and constructed,and should be maintained in a clean and reliable fashion. It should fit comfortably, encouraging worker use.If the personal protective equipment does not fit properly, it can make the difference between being safelycovered or dangerously exposed. Personal protective equipment (PPE) limits the health care workers contactwith all secretions or biological products. This study was planned to find gaps between use of PPE amongthe health care providers (HCPs) in Pune city.Methods: A cross sectional design was used to assess the usage of PPE among health care workers selectedby purposive sampling. The Data were collected by pretested structured questionnaire. Data analysis wasdone using SPSS 20 version at 5% of level of significance.Results: 60 Health care workers were participated in study. Among them, there were 38.9% doctors, 51.9%nurses and 9.2% were technicians. 18.1% health care workers who work outside the ICU had appropriateuses of PPE. It was high among doctors 31.5% followed by nurses 9.3% and technicians 8.2%. which wasstatistically significant p=0.001.Conclusions: The study showed inappropriate use and poor usage and practice of PPE among HCWs.
Keywords: Personal protective equipment, Health care providers, Infection control